A review of diaphragm walls (Institution of Civil Engineers, 1977)
Topics discussed in these papers include an analysis of available methods for designing diaphragm walls and anchored walls, practice in the detail design applications of diaphragm walls and contiguous piling, and design and control of bentonite/clay suspensions and concrete in diaphragm wall construction.
'... the record of a seminar, held on 9-10 September, 1976, to discuss "Diaphragm walls and anchorages" ...' - title page verso.
Keywords: Diaphragm walls -- Congresses.; Anchorage (Structural engineering) -- Congresses.; elektronické knihy; electronic books